Celebrities Representation in Print Media Discourse: A Cognitive Approach - Jameel, Maarif (Abdul Media Literasi, 2024)
This research paper studies the cognitive aspect of the magazine's cover lines, which are employed to represent and present celebrities to the public. The present study aims to identify the conceptual metaphors and the cognitive function they fulfill in print media discourse, particularly the celebrity magazine category. Lakoff and Johnson 1980 is the model adopted for analyzing the data under study. The results of this paper revealed a scarcity of metaphorical language in magazine cover lines in general. Additionally, most conceptual metaphors have been spotted as confined to limited metaphor patterns and types. These are found geared towards unveiling facts related to a celebrity's private life. They are intended to arouse the readers' curiosity and encourage them to buy the issue.